Innovative production of highly porous carbon for industrial effluent remediation via microwave vacuum pyrolysis plus sodium-potassium hydroxide mixture activation. (20th January 2019) - Liew, Rock Keey; Chai, Carmil; Yek, Peter Nai Yuh; Phang, Xue Yee; Chong, Min Yee; Nam, Wai Lun; Su, Man Huan; Lam, Wei Haur; Ma, Nyuk Ling; Lam, Su Shiung
Abstract: This study reports a novel method using microwave vacuum pyrolysis combined with sodium-potassium hydroxide mixture (NaOH-KOH) activation to produce highly porous activated carbon (AC) from palm residue (i.e. palm kernel shell, PKS) – a solid residue constantly produced in large volume by palm industry. The yield and properties of AC produced were found significantly influenced by two key process parameters - type of activating agent and chemical impregnation ratio. The pyrolysis provided fast heating rate (60 °C/min), high temperature (607 °C), and short process time (35 min) to convert PKS into biochar, and the subsequent activation by NaOH-KOH mixture at 1.0 of chemical impregnation ratio resulted in 84 wt% yield of AC. The AC possessed high BET surface area (1320 m 2 /g) and highly porous structure formed by micro- and meso-pores, thus showing high adsorption capacity. The adsorption capacity of AC was examined via impregnation with nickel and aluminium atoms (termed "Ni/AC" and "Al/AC") followed by application in treating industrial effluent abundantly released from palm oil mill (termed 'palm oil mill effluent, POME). Both Ni/AC and Al/AC showed high removal efficiency in reducing the total suspended solid (TSS), oil and grease (O&G), biochemical (BOD) and chemical oxygen demand (COD) in POME. Higher removal efficiency on BOD and COD was observed for Ni/AC and Al/AC than normal AC (non-metallic AC). The production cost of AC using this pyrolysis method was estimated to be ranged from 4 to 10 USD/kg. The results show the exceptional promise of this pyrolysis method as an approach to transform PKS into highly porous AC for utilize as an adsorbent to treat POME. Graphical abstract: Highlights: Microwave vacuum pyrolysis combined with NaOH-KOH activation was reported. Two process parameters were examined for the yield and properties of AC produced. AC was upgraded into metallic AC (Al/AC and Ni/AC) to treat palm oil mill effluent. Metallic AC removed 85% of BOD and 89% of COD concentrations. Normal AC (non-metallic) showed higher removal rate of TSS (80%) and O&G (88%).